1994
DOI: 10.1590/s0102-311x1994000500002
|View full text |Cite
|
Sign up to set email alerts
|

Violência social sob a perspectiva da saúde pública

Abstract: Este artigo tem a finalidade de introduzir o leitor na temática da violência social, sob a perspectiva da Saúde Pública. Desenvolve-se analisando o tema no âmbito da sociedade, no campo da saúde expressa na mortalidade e morbidade. Termina refletindo sobre as propostas possíveis, setoriais, intersetoriais, interprofissionais e articuladas com a sociedade e os movimentos sociais.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
334

Year Published

1998
1998
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(379 citation statements)
references
References 18 publications
(18 reference statements)
1
44
0
334
Order By: Relevance
“…Osler et al (26) observed that, even after adjustment for variables such as birth weight and cognitive function, the inverse association between father's social class at the time of the infant's birth and mortality among young adult men (15 to 34 years) was slightly attenuated but continued to be present. In the 15-to 19-year subgroup, the deaths predominated among boys; 87% were due to external causes, with 70.4% being due to violence, in agreement with other studies (33)(34)(35)(36)(37)(38). Starting in the 1960 decade, in Brazil infectious and parasitic diseases gave way to external causes represented by traffic accidents and homicides as the main cause of mortality in some age ranges.…”
Section: Discussionsupporting
confidence: 91%
“…Osler et al (26) observed that, even after adjustment for variables such as birth weight and cognitive function, the inverse association between father's social class at the time of the infant's birth and mortality among young adult men (15 to 34 years) was slightly attenuated but continued to be present. In the 15-to 19-year subgroup, the deaths predominated among boys; 87% were due to external causes, with 70.4% being due to violence, in agreement with other studies (33)(34)(35)(36)(37)(38). Starting in the 1960 decade, in Brazil infectious and parasitic diseases gave way to external causes represented by traffic accidents and homicides as the main cause of mortality in some age ranges.…”
Section: Discussionsupporting
confidence: 91%
“…In this respect, the notion of honor or respect (the more preferred category among adolescents) can function as a currency whereby they negotiate their place, especially regarding the inequalities between the genders 29 . This is where hierarchical terminology appears, where the binomial "whore"/"red hot lover" refers to the prohibitions for the different means of expressing desire and sexuality between the sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Assim, o grupo mais intensamente atingido pela violência constitui-se de adolescentes e adultos jovens do sexo masculino, pobres e negros. 10 As relações entre violências e condições de vida não são unívocas nem lineares, o que tem levado a certo questionamento sobre os seus determinantes. 21 Como adverte Soares, 17 "quem atribui o envolvimento com o crime a necessidades econômicas freqüen-temente esquece o papel que a cultura, os valores, as normas sociais e os símbolos desempenham.…”
Section: Introductionunclassified